Why Is It Challenging to Apply Arm’s Length Principle on Intragroup Financing in Indonesia? A Tax Officials Perspectives - Wuryaningsih, Heni; Nuryanah, Siti (Jati: Jurnal Akuntansi Terapan Indonesia, 2024)
Directorate General of Taxes amends its supervision business process to require Account Representatives to conduct transfer pricing analysis. As an international standard, transfer pricing must adhere to the arm's length principle. This research aims to analyze the reasons why the arm’s length principle on intragroup financing is challenging to apply in Indonesia, as perceived by Account Representatives in Jakarta Special Regional Tax Office utilizing the ADKAR model. Questionnaires and interviews are used as triangulation techniques in the study. The results show that participants were aware of the importance of conducting transfer pricing analysis and expressed a desire to participate in bringing about business process changes. Participants' knowledge and ability were major barriers to the implementation of the arm's length principle in intragroup financing. The primary hurdle in regards to knowledge is the assessment of credit ratings, whereas the ability component concerns the accessibility and expertise in utilizing the requisite tools and resources. Potential solutions suggested to Directorate General of Taxes include providing a case-based approach for training and enhancing accessibility to acquire comparable data or taxpayer credit ratings.